The ribosome biogenesis protein Esf1 is essential for pharyngeal cartilage formation in zebrafish. (24th August 2018) - Chen, Jian‐Yang; Tan, Xungang; Wang, Zheng‐Hua; Liu, Yun‐Zhang; Zhou, Jian‐Feng; Rong, Xiao‐Zhi; Lu, Ling; Li, Yun
Abstract : Craniofacial malformations are common congenital birth defects and usually caused by abnormal development of the cranial neural crest cells. Some nucleolar ribosome biogenesis factors are implicated in neural crest disorders also known as neurocristopathies. However, the underlying mechanisms linking ribosome biogenesis and neural crest cell (NCC) development remain to be elucidated. Here we report a novel zebrafish model with a CRISPR/Cas9‐generated esf1 mutation, which exhibits severe NCC‐derived pharyngeal cartilage loss and defects in the eyes, brain, and heart. The expression of several typical NCC markers, including sox10, dlx2a, nrp2b, crestin, vgll2a, and sox9a, was reduced in the head of the esf1 mutants, which indicates that esf1 plays a role in the development of zebrafish NCCs. We demonstrate that, similar to the yeast, loss of esf1 in zebrafish leads to defects in 18S rRNA biogenesis and ribosome biogenesis. We also show strong upregulation of p53 signaling as well as apoptosis, and poor proliferation in mutants. Inactivation of p53 rescues the early tissue defects and pharyngeal cartilage loss observed in esf1 mutants, indicating that increased cell death and pharyngeal cartilage defects observed in esf1 mutants are mediated via upregulated p53 signaling pathways. Based on transplantation analysis, we found esf1 functions in NCC in a cell autonomous fashion. Together, our results suggest that esf1 is required for NCC development and pharyngeal cartilage formation. These studies provide a potential model for investigating the relationship between ribosome biogenesis defects and craniofacial neurocristopathies. Abstract : ESF1 is an evolutionarily conserved nucleolar protein and is required for 18S rRNA biogenesis. Here we showed that the zebrafish esf1 mutants present with failure to develop neural crest cell‐derived craniofacial skeleton, and the defects are mediated via upregulated p53 signaling pathways.